A garantia da publicidade no processo civil - Almada, Roberto José Ferreira de (2004)
Legitimacy and popular controlability of the courts activities depend on the respect to the so called guarantee of an open and public proceeding. The principle of the public proceeding, a fundamental right of the people and the parties vis-a-vis the judge and the State, actually is expressed on the right of defense (audiatur et altera pars) of the parties, which deserve suficient information on a way to participate on the relationship stablished with the representaive of the State, and also as a thecnical and political mechanism of public revelation of the acts done by the State on the exercise of jurisdiction – both of those elements, that make the substance of this fundamental principle, provide the desirable democratic spirit to the proceeding. The ideas related to the guarantee of publicity come from the principle of popular sovereignty, as soon as the people detains the exclusive power to run their lives and destinies. The activities executed by the State always must be founded on a popular delegation, also, and the delegates of the people must act only on the name of the people, what mean that they have to explain their actions to the comunity affected by them. It shows why and how the judiciary acts need to be explained to the universal auditorium, and shared with it, only way to get popular and intercomunicational legitimacy for them. As any other of the several fundamental guaranties of the proceeding, the principle of publicity comes from a minimun ethical standard elected by the people to justify the serenity of the interpersonal relationships and also, as soon as it shows the need to control and fiscalize the public administration, it cames from a democratic justification of the political power on a way to identify, on a civilized territory, the paradigmatic standard of legitimacy of the general acts of the State.On one hand, the rigth of defense reconized to be aplied to the parties, internal expression of the publicity, attends the democratic needs of proceeding on their own perspectives, while on the other hand, the external expression of the publicity satisfies the same need expressed by universal auditorium, whith envolves the entire community geographically involved by the jurisdiction. Considering that the full guarantee of the open and public proceeding is consagrated by the current constitutionalism, the legitimacy of the civil proceeding is gained only by the popular mechanisms of control and fiscalization typical of the participative and intercomunicational democracy, meaning the necessary respect to the basic standard of the public and socially shared revelation of the jurisdictional acts.